2016
DOI: 10.4103/2153-3539.179984
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparison of color normalization methods for epithelial-stromal classification in H and E images

Abstract: Context:Color normalization techniques for histology have not been empirically tested for their utility for computational pathology pipelines.Aims:We compared two contemporary techniques for achieving a common intermediate goal – epithelial-stromal classification.Settings and Design:Expert-annotated regions of epithelium and stroma were treated as ground truth for comparing classifiers on original and color-normalized images.Materials and Methods:Epithelial and stromal regions were annotated on thirty diverse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
2
36
1
Order By: Relevance
“…We introduced a scalar component to the classified image by measuring the color deviation of pixels about the mean for each tissue element. We found that this operation resulted in structure-specific intra-image variability not significantly different from the unnormalized image, and similar to that reported previously [17]. To test how well this residual variability reflects the original modulation of the image, we measured the normalized mutual information (NMI) between the normalized and unnormalized images in HSV space (Fig 5A, dark bars).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…We introduced a scalar component to the classified image by measuring the color deviation of pixels about the mean for each tissue element. We found that this operation resulted in structure-specific intra-image variability not significantly different from the unnormalized image, and similar to that reported previously [17]. To test how well this residual variability reflects the original modulation of the image, we measured the normalized mutual information (NMI) between the normalized and unnormalized images in HSV space (Fig 5A, dark bars).…”
Section: Resultssupporting
confidence: 81%
“…This analysis provided quantitative insight into the amount of color variability present in the original images and the variability that persisted after normalization, and has previously been used in other reports [17]. Despite the pursuit to significantly reduce unwanted inter-image variability, an ideal for most color normalization algorithms is that the inherent variability within images is preserved.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Detection and classification of disease Cruz-Roa et al (2014) Detection of invasive ductal carcinoma H&E CNN-based patch classifier Xu et al (2014) Patch-level classification of colon cancer H&E Multiple instance learning framework with CNN features Bychkov et al (2016) Outcome prediction of colorectal cancer H&E Extracted CNN features from epithelial tissue for prediction Chang et al (2017) Multiple cancer tissue classification Various Transfer learning using multi-Scale convolutional sparse coding Günhan Ertosun and Rubin (2015) Grading glioma H&E Ensemble of CNNs Källén et al (2016) Predicting Gleason score H&E OverFeat pre-trained network as feature extractor Kim et al (2016a) Thyroid cytopathology classification H&E, RM & Pap Fine-tuning pre-trained AlexNet Litjens et al (2016) Detection of prostate and breast cancer H&E fCNN-based pixel classifier Quinn et al (2016) Malaria, tuberculosis and parasites detection Light microscopy CNN-based patch classifier Rezaeilouyeh et al (2016) Gleason grading and breast cancer detection H&E The system incorporates shearlet features inside a CNN Schaumberg et al (2016) SPOP mutation prediction of prostate cancer H&E Ensemble of ResNets Wang et al (2016b) Metastases Sethi et al (2016) Comparison of normalization algorithms H&E Presents effectiveness of stain normalization for application of CNNs CNNs with classical machine learning approaches using handcrafted features. In chest X-ray, several groups detect multiple diseases with a single system.…”
Section: Chestmentioning
confidence: 99%